Capitalism, alienation, and critique : studies in economy and dialectics - Sørensen, Asger, 1960- (Studies in Moral Philosophy, 2018)
In Capitalism, Alienation and Critique Asger Sørensen offers a wide-ranging argument for the classical Critical Theory of the Frankfurt School, thus endorsing the dialectical approach of the original founders (Horkheimer, Adorno, Marcuse) and criticizing suggested revisions of later generations (Habermas, Honneth). Being situated within the horizon of the late 20th century Cultural Marxism, the main issue is the critique of capitalism, emphasizing experiences of injustice, ideology and alienation, and in particular exploring two fundamental subject matters within this horizon, namely economy and dialectics. Apart from in-depth discussions of classical political economy and Hegelian dialectics, the explorative and inclusive argument also takes issues with Émile Durkheim's theory of value, the general economy of Georges Bataille and the dialectics of Mao Zedong.